Evaluation of the Food Security Program in Sidoarjo Regency - Rustianingsih, Eni (Universitas Muhammadiyah Sidoarjo, 2024)
The increase in Indonesian rice imports in 2023 reflects a shortage in the supply of rice food. The irony is that Indonesia is an agricultural country that wants to be self-sufficient in food. To achieve this, good synergy is needed between the Central Government and Regional Governments, including the Sidoarjo Regency Government. This research aims to evaluate the food security program implemented in Sidoarjo Regency, with a focus on the availability of rice and obstacles in meeting food needs. The method used is qualitative research with a library research approach, which involves collecting data through observation and documentation. The research results show that the availability of rice in Sidoarjo Regency will fluctuate from 2018 to 2024, with total rice production reaching 195,855 tons of GKG in 2023. Even though there is a rice surplus of 117,451 tons, challenges such as land conversion and unfavorable weather conditions remain obstacles in increasing agricultural productivity. The conclusions of this research emphasize the need for integrated policies and community support to increase rice food security in Sidoarjo Regency, as well as the importance of ongoing evaluation of existing programs to ensure the sustainability of food supplies in the future.